(untitled) (Research, Society and Development, 2022)
Acute pancreatitis (AP) is one of the most common emergencies causes of hospitalization for gastrointestinal diseases. Many studies in different countries have been performed to identify the etiology, pathomechanisms and therapeutic strategies for AP treatment. This systematic review perform a global analysis of knowledge production about AP. The SCOPUS database using for our systematic review. The study considers the period between 2016 and 2020 and considered scientific journals with respect to the subject of publications, quantity of studies published, citations and leading countries in this area of research. A total of 75 publications were eligible among 16,563 records in the database. The subjects most discussed in the articles is the search for new drugs and therapies for the treatment of AP is a central concern of the researchers involved in the study of AP (26.6%). The etiology of AP corresponded to n = 11 articles (14.6%), highlighting the recent focus on the causes of AP such as hypertriglyceridemia (HTG). The results show that AP is becoming a globalized subject. Altogether, institutions from 36 countries contributed to the knowledge of pancreatitis over the period considered. The USA has the most publications (20) and occupies the vanguard position on the subject. China is the second largest center in AP knowledge production (17). The recent evidence in the form of systematic reviews represent a viable tool to understand the patterns in knowledge production about AP and to identify gaps in the networks about the subject.